Distribution And Taxonomy of Paeonia - Dang Yu Lei; Rustamjon ALLABERDIEV; Nurbek KUCHKAROV (Academia One Publishing, 2023)
Peonies are rich and bright in color, and they also have important medicinal value. This article introduces the distribution of peony around the world, the classification of the genus Paeonia and the classification of Paeonia officinalis L., further elaborates on peony from a taxonomic perspective, and provide a theoretical basis for the popularity of peony, a promising plant, around the world.
Keywords: peony; Paeonia; Paeonia officinalis L; classification